(untitled) (Research, Society and Development, 2020)
Epidermal cysts are benign pathologies that can be developed anywhere in the body. It is a developmental cystic malformation, which occurs with low frequency, being rare in the oral cavity and represents about 0.01% of all cysts in the oral cavity. The objective of this article is to report the case of a male patient, 16 years old, with a history of swelling in the region of mouth floor with cervical exteriorization since he was 2 years old, clinically showing dysphagia, dyslalia, aesthetic and functional complaints. The chosen surgical treatment was total enucleation of the lesion under general anesthesia. Histopathological evidence showed the presence of a cystic wall covered by orthoceratinized stratified epithelial tissue with areas of intraluminal keratin flaking and absence of cutaneous appendages, favoring the diagnosis. Surgical enucleation by removing the entire epithelium from the cystic capsule is an appropriate therapeutics.